Multi-Dimensional Enhanced Seizure Prediction Framework Based on Graph Convolutional Network - Chen, Xin; Zheng, Yuanjie; Dong, Changxu; Song, Sutao (Frontiers in Neuroinformatics, 2021)
In terms of seizure prediction, how to fully mine relational data information among multiple channels of epileptic EEG? This is a scientific research subject worthy of further exploration. Recently, we propose a multi-dimensional enhanced seizure prediction framework, which mainly includes information reconstruction space, graph state encoder, and space-time predictor. It takes multi-channel spatial relationship as breakthrough point. At the same time, it reconstructs data unit from frequency band level, updates graph coding representation, and explores space-time relationship. Through experiments on CHB-MIT dataset, sensitivity of the model reaches 98.61%, which proves effectiveness of the proposed model.